[OP.1A.02] SELF-MEASUREMENT OF ORTHOSTATIC HYPOTENSION: FEASIBILITY AND ACCURACY. (September 2016) - Duron, E.; Vidal, J.S.; Roca, F.; Caillard, L.; Chaussade, E.; Chauvelier, S.; Rananja, H.; Boully, C.; Rigaud, A.S.; Hanon, O.
Abstract : Objective: Background: Orthostatic hypotension (OH) is associated with falls and mortality in the elderly. Self-measurement of blood pressure (SMBP) is validated to detect hypertension but feasibility and accuracy of self-measurement of orthostatic-hypotension (SMOH) is unknown. Objective: To evaluate feasibility and accuracy of SMOH or OH measured by caregiver among elderly subjects with memory complaints. Design and method: Hundred eighty-five patients attending a Broca's memory clinic, aged >60 years old, able to stand up for >3 minutes and with a Mini Mental State Examination > 25/30 or with a caregiver able to perform standardized BP measurement were included. OH was first sought at the memory clinic. Subjects or caregivers were instructed on SMOH detection procedure and lent validated devices. BP was measured three consecutive times, after 10 minutes of rest in sitting position and after 1 and 3 minutes of standing, in the morning and in the evening during 3 consecutive days and BP results written down on a standardized data sheet. Feasibility was evaluated according to the ability to properly fill in the data sheet, OH prevalence according to OH occurrence at 3 minutes compared with the last BP in sitting position. Results: Mean age was 79.3 (7.9) years old, 62.7% were women and mean MMSE was 24.4 (5.4)/30. OH was detected in 14.8% patients at the memory clinic and was associated with falls (65.2% vs. 30.4%, p = 0.03) and symptoms of OH (69.6% vs. 35.3%, p = 0.004). SMOH detection procedure was successful in 139 (75.1%) patients (59% self-measurement and 41% caregiver measurement) and was associated with male gender (p = 0.05). Cumulative prevalence of SMOH was 46%, 25.9%, 9.4%, 5.0%, 3.6%, 1.4% and 0.7% of patients had 1, 2, 3, 4, 5 and 6 SMOH episodes respectively. SMOH determinants were heart failure (p = 0.02), >4 medications (p = 0.04), low albumin level (p = 0.02) and low hand grip (p = 0.002). SMOH was marginally associated with OH detected at the memory (p = 0.10). Conclusions: SMOH prevalence is very high in elderly subjects. Predicative value of this SMOH for unfavorable outcome ought to be investigated in a prospective study.